Porous PES and PEI hollow fiber membranes in a gas-liquid contacting process-A comparative study - Bakeri, Gholamreza (Elsevier, 2015)
Porous polyetherimide (PEI) and polyethersulfone (PES) hollow fiber membranes were spun under the same spinning conditions and the fabricated membranes were characterized using various analytical methods. The membranes were then subjected to gas–liquid contactor experiments. While the PEI casing solution was thermodynamically less stable, the PES casting solution was less viscous which resulted in a more porous membrane structure. The mean pore size and effective surface porosity obtained by the gas permeation test showed superior properties of the PES membrane. Both PEI and PES membranes had sufficiently high LEPw values even though both polymers were known to be relatively hydrophilic, most likely due to their small pore sizes. The absorption flux of the PES membrane was 4.4×10-3 mol m-2 s-1 at the liquid flow velocity Vliquid of 1.8 m s-1, which was 267% higher than that of the PEI membrane (1.2×10-3 mol m-2 s-1) due to the larger pore size and smaller tortuosity of the PES membrane.